2015
DOI: 10.1016/j.tcs.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biological regulatory networks from Process Hitting models

Abstract: Qualitative formalisms offer a well-established alternative to the more traditionally used differential equation models of Biological Regulatory Networks (BRNs). These formalisms led to numerous theoretical works and practical tools to understand emerging behaviors. The analysis of the dynamics of very large models is however a rather hard problem, which led us to previously introduce the Process Hitting framework (PH), which is a particular class of nondeterministic asynchronous automata network (or safe Petr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Even if it already exists a few hybrid formalisms like time Petri Nets, hybrid automata, etc..., we propose this extension of the AN framework for several reasons. First, AN is a general framework that, although it was mainly used for biological networks [23,9], allows to represent any kind of dynamical models, and converters to several other representations are available. Indeed, a T-AN is a subclass of time Petri nets [10].…”
Section: Definition 8 (Active Timed Local Transitions)mentioning
confidence: 99%
“…Even if it already exists a few hybrid formalisms like time Petri Nets, hybrid automata, etc..., we propose this extension of the AN framework for several reasons. First, AN is a general framework that, although it was mainly used for biological networks [23,9], allows to represent any kind of dynamical models, and converters to several other representations are available. Indeed, a T-AN is a subclass of time Petri nets [10].…”
Section: Definition 8 (Active Timed Local Transitions)mentioning
confidence: 99%
“…Nevertheless, there are advances in computer science that could solve the state space size problem. In particular, the methodology known as Process Hitting appears to be a viable solution to the problem, since it is capable of obtaining information from immensely large networks without being limited by the problem of the size of the state space ( Folschette et al, 2015 ; Sheikh et al, 2019 ). Although this technique is still being experimented, it is not ruled out as a viable solution in the medium-term ( Sheikh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that our framework can encode them equivalently. In some cases, it is also possible to convert the obtained reduced automata network back to functional specification, for instance using [46].…”
Section: Discussionmentioning
confidence: 99%